Re: Andrea Necchi, Félix Guerrero-Ramos, Paul L. Crispen, et al. Gemcitabine Intravesical System plus Cetrelimab or Cetrelimab Alone as Neoadjuvant Therapy in Patients with MIBC: Primary Analysis and Biomarker Results of SunRISe-4. J Clin Oncol. In press. https://doi.org/10.1200/JCO-25-02382 - Giuseppe Di Lorenzo; Carlo Buonerba (European Urology Oncology, 2026)
Purpose Adjuvant radiotherapy for node-positive breast cancer (BC) using 50Gy/25fx has been Danish Breast Cancer Group (DBCG) standard. Hypofractionated radiotherapy based on 40Gy/15fx has been increasingly used; however, it is less frequently for locoregional therapy because of concern over more morbidity. DBCG Skagen trial 1 hypothesized that 40Gy/15fx did not cause more lymphedema than 50Gy/25fx 3 years after radiotherapy without compromising the pattern of failure. Methods Skagen trial 1 is a phase III, noninferiority trial randomly assigning high-risk BC patients with an indication for locoregional radiotherapy to standard 50Gy/25fx versus experimental 40Gy/15fx. The primary end point was arm lymphedema; assuming a 3-year incidence with 50Gy/25fx of 10%, noninferiority was predefined to maximum 5% excess incidence with 40Gy/15fx. Accrual continued until 3-year estimates were reported in 1,012 patients. Results Between 2015 and 2021, 2,963 patients consented from 17 centers; the intention-to-treat cohort comprised 2,908 patients: 1,444 had 50Gy (50%), and 1,464 had 40Gy (50%). The median age was 57 years (range, 23-86). At a median follow-up of 4.1 years (IQR, 3.0-5.0), the 3-year rates of lymphedema were 9.4% (50Gy) versus 8.0% (40Gy), odds ratio 0.84 (95% CI, 0.62 to 1.14), and P = .27, thus within the +5-percentage-point noninferiority margin. The median follow-up for cancer outcomes was 5.25 years (IQR, 4.26 to 6.96). Within 8 years, the hazard ratio for locoregional recurrence was 0.96 (95% CI, 0.62 to 1.51), that for distant recurrence was 1.10 (95% CI, 0.89 to 1.37), that for BC mortality was 1.25 (95% CI, 0.93 to 1.66), and that for all-cause mortality was 1.08 (95% CI, 0.85 to 1.36), thus all with no differences by random assignment. Conclusion 40Gy/15fx for locoregional radiotherapy of BC did not result in more lymphedema compared with 50Gy/25fx. There were no differences in locoregional or distant recurrences, breast cancer mortality, nor all-cause mortality between the random assignment arms.